Cholecystokinin and Trypsin Responses of Larval Red Drum (Sciaenops Ocellatus) to Soluble Components of Rotifers (Brachionus Plicatilis) and Algae (Isochrysis Galbana) - Webb, Ken; Holt, Joan (Avances en Nutrición Acuicola, 2008)
In an attempt to better understand the problems in weaning larval fish to artificial diets, our lab has begun to investigate the role of the digestive hormone cholecystokinin (CCK). While there are a number of other labs also investigating CCK and other digestive hormones such as bombesin, PPY, and gastrin; research into the roles of these hormones in fish is still in its infancy. Previous research with red drum larvae suggests that some component of rotifers and algae enable red drum larvae to more efficiently utilize microparticulate diets than when these are not included in the culture system. The current study investigated the impact of soluble components of rotifers and algae on the CCK and trypsin responses of larval red drum at 6 and 10 days post hatch (DPH). Introduction of homogenized rotifers was shown to significantly increase whole body CCK levels, CCK mRNA, and trypsin activity in 6 DPH red drum larvae, but not in 10 DPH larvae. Homogenates of Isochrysis galbana did not significantly affect CCK or trypsin at either age. This research suggests that there is a soluble component of rotifers that can upregulate digestive function in larval red drum, at least in 6 DPH larvae.